2003
DOI: 10.1021/jf0343884
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Cadmium from In Vitro Digested Infant Food Studied in Caco-2 Cells

Abstract: The solubility and bioavailability of cadmium (Cd) in infant foods, three cereal- and milk-based diets and two ready-to-use baby dishes, were studied after in vitro digestion and by using human intestinal Caco-2 cells. The solubility of Cd after in vitro digestion varied between diets; liver casserole had the highest solubility and was lower after infant as compared to adult digestion conditions. Generally, more Cd was soluble in infant intestinal than gastric juice in contrast to the results from the adult di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 22 publications
(21 reference statements)
0
6
2
1
Order By: Relevance
“…For example, Fu and Cui reported that the bioavailability of Cd ranged from 4.0-15.9% for the vegetables (Fu and Cui, 2013). However, the bioavailability of Cd in the present study was higher or lower than some other studies reported on CdCl 2 solution and infant food (Eklund et al, 2003;Chan et al, 2007). Besides, in an in vivo experiment, the bioavailability of Cd was 0.8% and 0.6% in the kidneys and livers of rats, respectively (Yannai and Sachs, 1993).…”
Section: Retention and Transport Of CD In Caco-2 And Mdck Cellscontrasting
confidence: 78%
“…For example, Fu and Cui reported that the bioavailability of Cd ranged from 4.0-15.9% for the vegetables (Fu and Cui, 2013). However, the bioavailability of Cd in the present study was higher or lower than some other studies reported on CdCl 2 solution and infant food (Eklund et al, 2003;Chan et al, 2007). Besides, in an in vivo experiment, the bioavailability of Cd was 0.8% and 0.6% in the kidneys and livers of rats, respectively (Yannai and Sachs, 1993).…”
Section: Retention and Transport Of CD In Caco-2 And Mdck Cellscontrasting
confidence: 78%
“…Effect of cadmium exposure on metals accumulation in cadmium long-term exposed Caco-2 TC7 cells (mg/kg). Pigman Jumarie et al 1999;Tallkvist et al 2001;Eklund et al 2003), copper (Rossi et al 1996;Ferruzza et al 2000), manganese (Yanagiya et al 2000), and zinc (Jovani et al 2001) among another. Furthermore, the TC7 clone offers noticeable advantages over parental Caco-2 cells and represents a good alternative to the parental line for drug transport studies (Le Ferrec et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro digestion in combination with exposure of Caco-2 cell monolayers to supernatants of the YS and CS cabbage digests appears to be a promising model for studying the bioavailability of different Cd levels in Chinese cabbage. The Caco-2 model has been previously used to evaluate bioavailability of Cd in the raw and cooked leafy vegetables [ 21 ] and infant food [ 38 ] concluding that Caco-2 cell assays offer an improved indicator of bioavailability than solubility. The current study reported that monolayers incubated with bioaccessible fractions of YS cabbage had significantly higher Cd bioavailability (cellular uptake %) as compared to CS cabbage ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The current study reported that monolayers incubated with bioaccessible fractions of YS cabbage had significantly higher Cd bioavailability (cellular uptake %) as compared to CS cabbage ( Table 2 ). Previous studies reported that 25%, 4–15.9%, and 3.8–6.3% of Cd were up taken by Caco-2 cells from CdCl 2 solution, leafy vegetables, and infant food [ 21 , 38 40 ]. In our study, the Cd bioavailability ranged from 1.12% to 14.66% for the YS and CS cabbage; these values were both lower and higher than those reported in previous studies [ 21 , 38 , 39 ] but in YS cabbage and at higher Cd level (9 mg kg −1 ) in CS cabbage, this is not in agreement with the previously reported approximate 5% gastrointestinal absorption of Cd from food [ 41 ].…”
Section: Discussionmentioning
confidence: 99%